Legal services and digital infrastructures : a new compass for better governance - Piana, Daniela (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book seeks to provide and promote a better understanding and a more responsive and inclusive governance of the automation and digital devices in public institutions, particularly the law and justice sector. Concerns related to AI design and use have been exacerbated recently with the recognition of the discriminatory potential that can be embedded into AI applications in public service institutions. This book examines issues relating to the assigning of responsibility in a public service produced and delivered on the basis of an automated mechanism. It encourages critical thinking about the legal services and the justice institutions as they are transformed by AI and automation. It raises awareness as to the prospect of transformation we face in terms of responsibility and of agency and the need to design a citizen-centered and human rights compliant system of technology assessment and AI monitoring and evaluation. The book calls for a comprehensive strategy to enable professional practitioners and decision makers to engage in the design of AI driven legal and justice services. The work draws on on-going research and consulting activities carried out by the author across different countries and different systems in the legal and justice sector. The book offers a critical approach to encourage a new mindset among legal professionals and the justice institutions thus empowering and training them to develop the necessary responsiveness and accountability in the justice sector and legal systems. It will also be of interest to researchers and academics working in the area of AI, Public Law, Human Rights and Criminal Justice"--
Sailing in open sea -- Reframing the digital picture -- In search of fairness -- Kinds of intelligence in the justice system -- Leverages of change in the justice system -- A new compass for legal professionals, stakeholders, and policy makers.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Law and legislation; Artificial intelligence -- Law and legislation -- Criminal provisions; Digital communications -- Law and legislation; Technological innovations -- Law and legislation; COMPUTERS / General; LAW / General; LAW / Civil Rights